IMPLEMENTATION OF TPM ( TOTAL PRODUCTIVE MAINTENANCE) METHOD ON FILLING LINE 4 MACHINE TO REDUCE REJECTS AND DOWNTIME AT PT.XYZ - khusaeri (Department of Industrial Engineering - Universitas Yudharta Pasuruan, 2024)
XYZ is one of the manufacturing companies engaged in various kinds of cold drinks (beverages), located in Pasuruan regency. In this study, the focus is on the problem of waste defects or product defects in filling line 4 which results in decreased production quality and production targets that cannot be achieved, which results in many losses for the company because of the costs that have been incurred but the results are not according to the target. In the production process on line 4, there are often irregularities in the machine, especially in the filling machine which often experiences throubleshoot, resulting in a lot of waste defects that result in the production target not being achieved. Therefore, analysis and planning for machine repair are needed to reduce or eliminate engine downtime in the filling machine due to the stamp stuck in the line and resulting in product defects or waste defects. In an effort to reduceor eliminate engine downtime and waste defects, using the total productive maintenance (TPM) method, fishbown diagram, and 5W1H method but with certain stages and using lean tools to repair the machine.